Application of Centrifuge Combined with Biodiesel Washing Machine with Biochar in Biodiesel Production - Fonghiransiri, Surasak; Chungcharoen, Thatchapol; Choola-aied, Orasa; Limmun, Warunee (My University, 2025)
This research focused on the application of a centrifuge combined with a biodiesel washing machine with biochar in biodiesel production. This method aims to reduce the amount of biochar used in the washing process to meet biodiesel standards. Therefore, the research aimed to improve the biodiesel production process by using a centrifuge machine combined with the biochar washing method (CB) and comparing it with two methods: gravitational settling combined with water washing (GW) and gravitational settling combined with biochar washing (GB). The results indicated that the CB method could reduce contaminants in biodiesel. Although the biodiesel yield did not differ from the GB method, it remained higher than the GW method, increasing the biodiesel yield by up to 1.19% (90.24%). Furthermore, the CB method was more effective in removing acidity, water content, methanol, and glycerol in biodiesel compared to the GB method, with removal percentages of 63.88%, 79.49%, 99.70%, and 85.19% respectively. Consequently, this led to a decrease in viscosity (3.998 cSt) and density (865.93 kg/m3). This method provides biodiesel properties that meet biodiesel standards.
Keywords: Biodiesel; Biodiesel washing machine; Centrifuge machine